VR games in metaverse 1 - Wee, Noel Ee Cher (Nanyang Technological University, 2025)
Singapore’s rapidly aging population faces mounting challenges associated with cognitive decline and loneliness. In order to address these issues, this project introduces “Monster Snap”, a double-pronged Virtual Reality (VR) game designed to mitigate said issues by providing cognitive stimulation and fostering social interactions for its target demographic, elderly individuals suffering from dementia and social isolation. Built using Unity, “Monster Snap” leverages on interactive photography-based gameplay, avatar customisation and competitive elements. The game is grounded in theoretical frameworks such as Cognitive Stimulation Theory (CST), Social Cognitive Theory (SCT), and Reminiscence Therapy, ensuring its design aligns with the target demographic’s needs by stimulating memory recall, promoting social interaction, and enhancing emotional well-being. Due to constraints in direct user testing, the game’s effectiveness is assessed through theoretical benchmarking and a preliminary usability study with an elderly participant. While initial results highlight the game’s potential benefits, future improvements include incorporating expanded language options, readjusting difficulty settings and partnerships with healthcare institutions to conduct testing with the game’s target demographic, in order to refine its accessibility and therapeutic impact.